Management of critical pests and diseases through enhanced risk assessment and surveillance and understanding climate impacts through enhanced modeling - Kroschel, Jürgen; Beed, Fenton D.; Garrett, K.A.; Coyne, D.; Etten, Jacob van; Forbes, G.; Herrera, B.; Kreuze, J.; Parsa S; Sparks, Adam H.; Tamo, Manuele; Subramanian S; et al. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The workshop was conducted from 10-14 December, 2012 at the International Potato Center, Lima, Peru. It was jointly funded by the research programs on Roots, Tubers, and Banana (RTB) and on Climate Change, Agriculture and Food Security (CCAFS). The workshop successfully linked scientists from CG-Centers (Bioversity, CIAT, CIMMYT, CIP, ICRISAT, IITA, and IRRI) and other stakeholders (CABI, FAO, FERA, icipe, UC Davis, University of Leeds, Kansas State University, Ohio State University) working in pest and disease management. Discussions focused on challenges and opportunities to synergize expertise towards improving risk assessments of pests and diseases under current and changing climates in order to target surveillance initiatives as well as to share experiences and develop joint modeling approaches to better understand the effects of climate change on agricultural pests, diseases and crop losses.